Temperature evolution during tensile test of TiNi shape memory alloy - Gadaj, S.P.; Nowacki, W.K.; Tobushi, H. (Archives of Mechanics, 1999)
Experimental results containing both the mechanical characteristics and the changes of temperature obtained during tensile test of TiNi shape memory alloy strained at various strain rates have been presented. The investigations were carried out at room temperature (≈ 295 K) and at chamber temperature equal to 333 K. The temperature changes were measured in a contactless way by recording the infrared radiation emitted by the surface of the sample. It was found that during loading at room temperature, the phase transformation process is homogeneous but at temperature 333 K the process seems to be heterogeneous. The martensitic transformation was accompanied by an increase in temperature. Both the stresses and the temperature changes were higher for the tests carried out at elevated temperature. Decreases in temperature during unloading were higher too. For tests carried out in the same conditions, the temperature increments in the range of the martensitic transformation plotted as a function of stress, turned out to lie on the same curve, independently of the strain rate.